Projection neurons in the cortex and hippocampus: differential effects of chronic khat and ethanol exposure in adult male rats - Alele PE; Matovu D; Imanirampa L; Ajayi AM; Kasule GT (Dove Medical Press, 2016)
Paul E Alele,1 Daniel Matovu,1 Lawrence Imanirampa,2 Abayomi M Ajayi,3 Gyaviira T Kasule,4 1Department of Pharmacology and Therapeutics, 2Department of Pharmacy, Faculty of Medicine, Mbarara University of Science and Technology, Mbarara, Uganda; 3Department of Pharmacology and Therapeutics, Faculty of Basic Medical Sciences, College of Medicine, University of Ibadan, Ibadan, Nigeria; 4Department of Anatomy, Histology and Embryology, Faculty of Medicine, Mbarara University of Science and Technology, Mbarara, Uganda Background: Recent evidence suggests that many individuals who chew khat recreationally also drink ethanol to offset the stimulating effect of khat. The objective of this study was to describe the separate and interactive effects of chronic ethanol and khat exposure on key projection neurons in the cortex and hippocampus of young adult male rats. Methods: Young adult male Sprague Dawley rats were divided into six treatment groups: 2 g/kg khat, 4 g/kg khat, 4 g/kg ethanol, combined khat and ethanol (4 g/kg each), a normal saline control, and an untreated group. Treatments were administered orally for 28 continuous days; brains were then harvested, sectioned, and routine hematoxylin–eosin staining was done. Following photomicrography, ImageJ® software captured data regarding neuron number and size. Results: No differences occurred in counts of both granular and pyramidal projection neurons in the motor cortex and all four subfields of the hippocampal formation. Khat dose-dependently increased pyramidal neuron size in the motor cortex and the CA3 region, but had different effects on granular neuron size in the dentate gyrus and the motor cortex. Mean pyramidal neuron size for the ethanol-only treatment was larger than that for the 2 g/kg khat group, and the saline control group, in CA3 and in the motor cortex. Concomitant khat and ethanol increased granular neuron size in the motor cortex, compared to the 2 g/kg khat group, the 4 g/kg khat group, and the 4 g /kg ethanol group. In the CA3 region, the 4 g/kg ethanol group showed a larger mean pyramidal neuron size than the combined khat and ethanol group. Conclusion: These results suggest that concomitant khat and ethanol exposure changes granular and pyramidal projection neuron sizes differentially in the motor cortex and hippocampus, compared to the effects of chronic exposure to these two drugs separately. Keywords: cortex, ethanol, granular neurons, hippocampus, khat, pyramidal neurons, concomitant exposure